Factors Affecting Sleep Problems in Preschoolers - Wahyuningrum, Eka; Yulianti, Natalia Ratna; Gayatina, Andri K. (Nurse Media Journal of Nursing, 2020)
Background: Sleep problems are self-care deficits of sleep experienced by more than 44% of preschoolers. Some studies have showed that physical, psychological, family, environmental, and temperamental factors could cause sleep problems among children. However, other research showed that there is no correlation between sleep problems and environmental factors. There are pro-cons regarding the causes of sleep problems. Purpose: The purpose of this study was to analyze factors affecting sleep problems among preschoolers.Methods: A cross-sectional study was conducted among 297 preschoolers selected by systematic random sampling. Data were collected using the Children’s Sleep Habits Questionnaires (CSHQ) and analyzed using bivariate (Chi-Square and Fisher tests) and multivariate (logistic regression) analyses.  Results: Results of the bivariate analysis showed that some variables were related to sleep problems among preschoolers, including family income (p=0.027), the education level of the mother (p<0.001), and bed-sharing (p=0.003). Multivariate analysis found that factors related to sleep problems were bed-sharing (p=0.031; OR=2.377), gadget use in two hours before sleep (p=0.039; OR= 2.703), and the education level of the mother (p=0.007; OR=2.244).Conclusion: Factors related to sleep problems in preschoolers were bed-sharing, gadget use in two hours before sleep, the education level of the mother, and family income. This study recommends that environmental and family factors should be modified by limiting bed-sharing and reducing the use of gadgets before bedtime.